Case reportsAcute inferior myocardial infarction in a patient with a prosthetic aortic valve and high international normalized ratio - Atas, Halil; Sari, Ibrahim; Delil, Kenan; Ileri, Cigdem; Samadov, Fuad (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
ST elevation acute myocardial infarction in patients with a mechanical prosthetic valve is rare and usually due to inadequate anticoagulation. We present a case of acute inferior myocardial infarction in a patient with a prosthetic aortic valve and high international normalized ratio, which has not been reported previously.